2015
DOI: 10.1097/hp.0000000000000348
|View full text |Cite
|
Sign up to set email alerts
|

Lymphoid and Myeloid Recovery in Rhesus Macaques Following Total Body X-Irradiation

Abstract: Recovery from severe immunosuppression requires hematopoietic stem cell reconstitution and effective thymopoiesis to restore a functional immune cell repertoire. Herein, a model of immune cell reconstitution consequent to potentially lethal doses of irradiation is described which may be valuable in evaluating potential medical countermeasures. Male rhesus macaques were total body irradiated by exposure to 6.00 Gy 250 kVp x-radiation (midline tissue dose, 0.13 Gy min-1) resulting in an approximate LD10/60 (n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 57 publications
5
32
0
Order By: Relevance
“…NHP have been used in radiation dose response studies for many decades [ 9 11 , 17 , 46 ], focusing on the effects of mitigators on acute radiation syndromes of different organ systems and mortality. However, there have been few studies of the cellular and molecular level changes underlying these broad biological end-points.…”
Section: Discussionmentioning
confidence: 99%
“…NHP have been used in radiation dose response studies for many decades [ 9 11 , 17 , 46 ], focusing on the effects of mitigators on acute radiation syndromes of different organ systems and mortality. However, there have been few studies of the cellular and molecular level changes underlying these broad biological end-points.…”
Section: Discussionmentioning
confidence: 99%
“…The MCART consortium has developed and characterized animal models that define the incidence, latency, severity and onset of GI-ARS, H-ARS, and MOI involving the kidney, lung, and heart (Farese et al 2012;Jackson et al 2012;Plett et al 2012;Garofalo et al 2014;de Faria et al 2015;Farese et al 2015;Medhora et al 2015;Zhang et al 2015;Cohen et al 2017). Histological, clinical, and analytical techniques were used to interrogate mechanisms of action (MoA) and identify biomarkers of radiation injury following all-cause mortality (Booth et al 2012a;Chua et al 2012;MacVittie et al 2012a;Jones et al 2014a;Jones et al 2014b;Carter et al 2015;Farese et al 2015;Jones et al 2015;Zhang et al 2015;Carter et al 2016;Carter et al 2017;Cohen et al 2017;Jones et al 2017). While these studies have provided vital mechanistic 'pieces of the puzzle' and identified panels of biomarkers that can be used to assess injury and efficacy of a MCM, they cannot inform on the natural history of injury development.…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with prior observations from lymphopenic mice, humans, and irradiated NHPs. 19,39 Although peripheral expansion can lead to constriction of TCR diversity, 39 we did not observe a significant change in TCR sequence entropy once the memory:naïve cell balance returned to baseline, suggesting any TCR skewing was transient.…”
Section: Discussionmentioning
confidence: 64%
“…Given these complications, the rhesus macaque nonhuman primate (NHP) model is often used for evaluation of immune function and radiation countermeasures. [19][20][21][22][23] Importantly, the rhesus immune system closely recapitulates that of humans, and NHPs are susceptible to many human pathogens and simian pathogens that are similar to human pathogens. Further, NHPs are inherently susceptible to inflammation-associated morbidities found in humans such as obesity and hypertension.…”
Section: Introductionmentioning
confidence: 98%